FOOTBALL - Neves, Leonardo de Lima; Silva, Leandro José Pereira da; Maciel, Sirlei de Andrade (Encontro Internacional de Gestão, Desenvolvimento e Inovação (EIGEDIN), 2020)
In addition to its clear economic importance, football also has social importance. The need to professionalize the management of football clubs has demanded studies from the academic environment, including the research that aims to relate economic and financial aspects. About this, the present study aimed to verify which are the most evident financial indicators in the studies that analyze football clubs. Therefore, a systematic review with the PRISMA methodology was adopted, carried out on the Scopus and Web of Science databases. The keywords were defined, emphasizing that there was no time frame and 141 (Scopus - 49 and Web of Science - 92) studies were found, which, after being selected, resulted in 9 articles to be investigated. From this, the profile of the publications was described, identifying objectives, methodological procedures and main results.